Chapter Introduzione - Bulli, Giorgia (Studi e saggi, 2021)
Migration is a highly debated issue in political but also academic terms. Research on the national and international level is more and more sophisticated and detailed in the selection of the case studies. In this scenario, the authors of this volume aim to present to the academic attention and to the community of university students a multi-disciplinary approach to the analysis of migration in Italy, whose main purpose is to go beyond the over-adopted concept of migration as social, political and cultural "challenge"